The soft power of Chinese law - Erie, M (Columbia Journal of Transnational Law Association, Inc., 2023)
Previous major capital-exporting nations have attained hegemony through a combination of coercion, currency, and contracts. In particular, the United Kingdom and the United States developed globe-spanning navies and modern militaries, their denominations are amongst the strongest in the world with the US dollar serving as global world currency, and common law has become standard as the choice of law in international contracts. China marks an exception. The People’s Republic of China (PRC) is mainly an economic superpower, one that (as of yet) lacks military predominance or financialization, although China is quickly promoting both. Likewise, Chinese law has been mostly peripheral to China’s rise. Chinese parties may just as likely choose English law over PRC law for their contracts. Nonetheless, as with its navy and the internationalization of the renminbi, China is also advocating for the use of Chinese law for international business. Pre-existing models to understand how China is doing so, mainly, those based on the English or American experiences, mostly miss the mark. Rather than underwriting hard power, law in the Chinese case functions to boost China’s soft power: its ability to align the interests of host states with its own. This Article is the first to conceptualize the role of law in China’s world-wide soft power. It does so by taking a deep dive into the first legal institution, and specifically, dispute resolution institution, the PRC has co-created outside of the PRC: the China-Africa Joint Arbitration Center (CAJAC). Based on qualitative data collected from both China and partner states in Africa, CAJAC provides an example of the exercise of Chinese law as soft power, its aims, and also provides a basis for analyzing some of its potential effects. Specifically, as with other soft power initiatives through international training and public diplomacy, law operates through international networks and is aimed to secure China’s economic and geostrategic interests. Importantly, the Article balances the Chinese view of the use of PRC law abroad with the perceptions of counterparts in African host states, views which are largely missing in the literature. The Article finds that law is one dimension of China’s emerging transnational ordering, yet as an instrument of governance, its effects may be ambivalent. While it has “hard edges” that secure Chinese trade and investment, it also demonstrates some of the shortcomings of domestic Chinese law as soft power, shortcomings which are amplified when Chinese law as soft power is deployed overseas.